Apport De La Teledetection Pour Le Suivi SpatioTemporel De L’occupation Du Sol Dans La Region Montagneuse Du Tonkpi (Cote D’ivoire) - Cyrille Bi Tiesse; Eboua Narcisse Wandan; Hyppolite Dibi N’da (European Scientific Journal, ESJ, 2017)
Objective: This study aims to characterize and to map vegetation cover in the mountainous region of Tonkpi in order to evaluate forest dynamics by remote sensing. Methodology and Results: This work relied on four satellite images of the scene 198-55 Landsat 4 TM 1990 from Landsat 7 ETM+ in 2000, Landsat 5 TM 2011 and Landsat 8 OLI-SHOTS 2015. Based on field data, classification was conducted using the maximum likelihood method in satellite images (OLI-SHOTS, ETM + and TM) in order to map vegetation from 1990 to 2015. These maps were superimposed to the Digital elevation model produced from an ASTER image in order to assess forest dynamics at altitude levels. The diachronic study of land use revealed a change in the landscape with a significant reduction of dense forest (-35.6%) and crop lands and fallow (-42.14%), and an increase of degraded forests (15.13%) and bare soil land and houses (10.46%). Moreover, high altitudes occupy a large proportion (37.7%) of the landscape (12,284 km2 ), followed by medium altitudes (34.6%), and low altitudes (27.7%). Concerning bare soil and homes, there is a large increase of the area at low altitudes (88, 96%) while concerning crops and fallow, the area reduction was more pronounced at high altitudes ( -53.64%). The medium altitudes have the highest rate of increase (51.14%) in degraded forests, and the highest decrease (-43.25%) in the dense forests. Conclusion and Application: The study shows that high altitudes occupy the largest proportion of the total area of the region and a change in the landscape due to human activities. Based on the results, we recommend a spatio-temporal monitoring of the net erosion on the mountains in order to maintain its agricultural potential and fight effectively against erosion.